The dawn of a discipline : international criminal justice and its early exponents / [edited by] Frédéric Mégret, McGill University, Montréal [and] Immi Tallgren, University of Helsinki. - Mégret, Frédéric; Tallgren, Immi (Cambridge University Press, 2020)
The history of international criminal justice is often recounted as a series of institutional innovations. But international criminal justice is also the product of intellectual developments made in its infancy. This book examines the contributions of a dozen key figures in the early phase of international criminal justice, focusing principally on the inter-war years up to Nuremberg. Where did these figures come from, what did they have in common, and what is left of their legacy? What did they leave out? How was international criminal justice framed by the concerns of their epoch and what intuitions have passed the test of time? What does it mean to reimagine international criminal justice as emanating from individual intellectual narratives? In interrogating this past in all its complexity one does not only do justice to it; one can recover a sense of the manifold trajectories that international criminal justice could have taken.